2021
DOI: 10.1088/1755-1315/637/1/012074
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of ascorbic acid content (vitamin C) of purslane (Portulaca oleracea L.) at various altitudes in East Java, Indonesia

Abstract: Purslane (Portulaca oleracea L.) is a weed that can be used as a source of natural antioxidants. One of the ingredients in purslane is ascorbic acid (vitamin C). One of the preventive measures related to infections caused by the coronavirus is taking vitamin C to support the body’s immunity, which is proven to have a positive effect on the body’s immunity. Vitamin C can prevent susceptibility to reduce respiratory infections in certain conditions. The objective of this study was to get purslane plants (Portula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
2
3
0
Order By: Relevance
“…Purslane is very rich in minerals and nutrients [43], as well as mustard and radish, but as purslane absorbs salts [44], this may explain the early calcium rise despite the plant's small size. These results are consistent with those of [45] in that the purslane plant is a strong absorbent of salts which agrees with [46] in that purslane is a plant rich in calcium.…”
Section: Calcium Contentsupporting
confidence: 90%
See 1 more Smart Citation
“…Purslane is very rich in minerals and nutrients [43], as well as mustard and radish, but as purslane absorbs salts [44], this may explain the early calcium rise despite the plant's small size. These results are consistent with those of [45] in that the purslane plant is a strong absorbent of salts which agrees with [46] in that purslane is a plant rich in calcium.…”
Section: Calcium Contentsupporting
confidence: 90%
“…It is clear from our research that vitamin C is initially available in all types of selected plants, and this seems appropriate because vitamin C is perhaps one of the most widespread vitamins among plants, which may seem compatible with its availability in all stages of germination and from the beginning, indicating its importance as a vital component for the plant in general. From the research results, it appears that purslane is superior to both radishes and brown mustard in vitamin C content, which is consistent with [43] in referring to the nutrient-rich purslane plant, which is also a rich source of vitamins in general, and also with [45], as their results report that purslane can be considered as a source of high-quality biologically active components of ascorbic acid (vitamin C) for therapeutic purposes in raising the body's immunity and increasing its resistance to viral infections, including covid-19. Also [52,53], in his description of nutritious foods, refers to the richness of purslane in vitamin C, an antioxidant and one of these vitamins available in the plant.…”
Section: Vitamin Csupporting
confidence: 85%
“…Our results showed that the ascorbic acid content of E. latifolia was lower than that reported from Sikkim by Dasila and Singh (71). This variation may be attributed to different analytical methods, as reported by Dias et al (72). The E. pyriformis reported in this study had a lower ascorbic acid content than that reported from Manipur (20.10 mg/100 g) by Khomdram et al (70).…”
Section: Functional Attributes and Antioxidant Activity 321 Ascorbic ...mentioning
confidence: 38%
“…The variations in genetic make-up among the species may be the cause of the variations in total carotenoids. Dias et al (72) have also reported the great influences of varieties, maturity, cultural management, environment, postharvest care, storage conditions, and analytical methods on the formation of secondary metabolites, including the total carotenoid content in fruit crops. The high carotenoid content of these fruits is an important indicator of their quality and high nutritional value (83).…”
Section: Total Carotenoid Contentmentioning
confidence: 99%
“…The future studies should be aimed at the methods for improved productivity, phytochemical composition, and its suitability for urban agriculture. Dewanti et al (2021) found the highest amount (9.73 mg kg −1 ) of vitamin C in purslane obtained from lowland areas.…”
Section: Domestication and Cultivation Of Purslane And Measures To Upscale Its Production And Consumptionmentioning
confidence: 83%